Pengaruh Kualitas Layanan, Harga dan Aksesibilitas Terhadap Loyalitas Melalui Kepuasan Wisatawan Sebagai Variabel Intervening Pada Objek Wisata Air Kabupaten Penukal Abab Lematang Ilir (Pali) - Juansya Juansya; Sri Rahayu; Tobari Tobari (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims to determine the Effect of Service Quality, Price and Accessibility on Loyalty through Tourist Satisfaction as an Intervening Variable in Water Tourism Objects in PALI Regency. This type of research is Associative. The sample in this study amounted to 97 selected using purposive sampling technique. The data used in this study are primary data with questionnaire data collection methods. The results of the study show that: (1) There is a significant influence between service quality, price and accessibility together on loyalty through tourist satisfaction as an intervening variable in water tourism objects in PALI district. (2) There is a significant influence between service quality, price and accessibility together on loyalty through tourist satisfaction as an intervening variable in water tourism objects in PALI district. (3) There is a significant influence between service quality, price and accessibility together on tourist satisfaction at water tourism objects in PALI district